Mesquite pods as a source of soluble carbohydrates in elephant grass silages - F. D. S. Ferreira; B. S. Garcez; V. M. Mascena; B. H. Maia; C. F. O. Pinho Filho; J. V. P. Silva; M. H. A. Lopes; S. A. A. Macedo (Boletim de Indústria Animal, 2021)
The objective of this study was to evaluate the fermentation parameters and chemical composition of elephant grass silage with inclusion of crushed mesquite pods, at the levels of 8, 16, 24 and 32% as a source of soluble carbohydrates, in addition to a control treatment (no mesquite pod). Fermentation parameters were evaluated for gas losses (GL), effluent losses (EL), dry matter recovery (DMR), pH, ammonia nitrogen (NH3-N), and chemical composition related to dry matter (DM), crude protein (CP), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicellulose (HEM), cellulose (CEL), lignin (LIG) and total digestible nutrients (TDN). A quadratic behavior (p<0.05) was found for GL, with a reduction of 45.58% with 32% inclusion. There was a decrease (p<0.05) in EL (59.22%) and NH3-N (38.21%) and an increase in DMR by 17.57% as the mesquite pod meal was added to the silage. As for the chemical composition, the inclusion of mesquite pod meal promoted increments (p<0.05) of 72.28%, 69.58% and 29.80% for the DM, CP and TDN, respectively, and a decrease in NDF (29.92%) and ADF (31.84%) up to the highest level of inclusion of mesquite pod meal (32%). The inclusion of up to 32% mesquite pod meal in elephant grass silage promotes better fermentation stability in the silo, by reducing losses and increasing the DM content of the ensiled mass, which minimizes nutrient leaching. The use of mesquite pod meal as a source of soluble carbohydrates can also improve the silage chemical composition, increasing the content of CP and TDN, and reducing the content of NDF, ADF and Lignin.